2017
DOI: 10.1002/bmc.3985
|View full text |Cite
|
Sign up to set email alerts
|

Contents variation analysis of free amino acids, nucleosides and nucleobases in semen sojae praeparatum fermentation using UFLC‐QTRAP MS

Abstract: UFLC-QTRAP MS was used to develop a sensitive and rapid method of evaluating content variation during Semen sojae praeparatum (SSP) fermentation. It did this through the simultaneous quantification of 22 free amino acids and 16 nucleosides and nucleobases in the raw materials and processed products of SSP. The method was shown to be reproducible and accurate. The limits of detection and quantity values were 0.09-168.75 and 0.31-562.50 ng/mL for the 38 analytes, respectively. The data were examined through prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Gln, Arg, and Asn accounted for higher percentage than the rest of FAAs for all FMP in the whole fermentation period, and all their percentages were above 10%, while values were moderate for Val, Phe, and Tyr, and low for His, Ile, and Glu. Chai, Cui, Shan, Yu, and Wen (2017) reported that Arg and Gln were the major FAAs in semen sojae praeparatum fermentation. Cuadra‐Crespo and Amor (2010) also found that Arg accounted for half of the total AAs content in fresh pepper.…”
Section: Resultsmentioning
confidence: 99%
“…Gln, Arg, and Asn accounted for higher percentage than the rest of FAAs for all FMP in the whole fermentation period, and all their percentages were above 10%, while values were moderate for Val, Phe, and Tyr, and low for His, Ile, and Glu. Chai, Cui, Shan, Yu, and Wen (2017) reported that Arg and Gln were the major FAAs in semen sojae praeparatum fermentation. Cuadra‐Crespo and Amor (2010) also found that Arg accounted for half of the total AAs content in fresh pepper.…”
Section: Resultsmentioning
confidence: 99%
“…As important hydrosoluble bioactive components, nucleosides, nucleobases, and amino acids possess multiple functions such as immunoregulation, anti‐oxidation, anticancer, obesity suppression, and blood pressure reduction . Considering multiple bioactivities and benefits for human health of these compounds, several analytical methods to detect them have been reported to assess the quality of food or medicinal materials . Nevertheless, abundance of nucleosides, nucleobases, and amino acids in different parts (all, head, body, and tail) of ASR from different regions has been rarely investigated, so that the highly efficient utilization of ASR resource is hindered.…”
Section: Introductionmentioning
confidence: 99%
“…More people are expected to consume SSP if the fermentation process includes quality assessment and quality control. Other studies have focused on the active ingredients in SSP, such as isoflavone [8,9,10,11], peptides [12], biogenic amines [13,14], and volatile components [15], the physiological properties of SSP such as anti-oxidative activity [16], anti-proliferative activity [17], anti-α-glucosidase activity [18] and anti-hypertensive effects [19], and species and quantities of fermenting bacteria in SSP spontaneous fermentation, such as bacterial fermentation and fungus fermentation [20,21]. However, no systematic comparison has been conducted of the active ingredients among the raw materials and the SSP products collected at different fermentation stages.…”
Section: Introductionmentioning
confidence: 99%